Effect of dietary supplementation of kanamycin on growth efficiency of crossbred female calves - PANDEY, POONAM; AGRAWAL, I S; PANDEY, A K (The Indian Journal of Animal Sciences, 2011)
Crossbred female calves (12) were divided into 2 groups. Both groups were fed on concentrate mixture and green oats, however, ration of group T2 was supplemented with kanamycin @ 20 ppm/head/day. The average daily body weight gain in groups T1 and T2 were 35.65±21.72 and 398.55±11.81 g/day and feed conversion efficiencies were 9.07±0.25 and 8.45±0.16 respectively. The DM and CP digestibility coefficients were higher in group T2, whereas NDF and ADF digestibility were lower in group T2. Thus, kanamycin as a feed additive, stimulates weight gain and improves feed conversion efficiency in crossbred female calves.